Patients with rectal cancer are satisfied with in-hospital communication despite insufficient information regarding treatment alternatives and potential side-effects. (3rd October 2018) - Walming, Sofie; Asplund, Dan; Block, Mattias; Bock, David; Gonzalez, Elisabeth; Rosander, Carina; Rosenberg, Jacob; Angenete, Eva
Abstract: Aim: Patients with rectal cancer may undergo treatment such as surgery and (chemo)radiotherapy. Before treatment, patients are informed of different options and possible side-effects. The aim of the study was to evaluate the patients' experience of communication with healthcare personnel at time of diagnosis and after one year. Method: A total of 1085 patients from Denmark and Sweden were included. They answered a detailed questionnaire at diagnosis and at the one year follow-up. Clinical data were retrieved from national quality registries. Results: Response rates were 87% at baseline and 74% at one year. Overall the patients were very satisfied with the communication with healthcare personnel. However, some patients reported insufficient information regarding treatment options and possible side-effects. Only 32% (335/1050) and 24% (248/1053), respectively, stated that they were informed about possible sexual and urinary dysfunction before treatment. Conclusions: Even though patients felt that they received insufficient information regarding side-effects on sexual and urinary function, they were generally satisfied with the communication with the healthcare personnel. Since overall satisfaction with the level of information was very high, it is unlikely that further information to patients with rectal cancer in the surgical and oncological settings will improve satisfaction with communication.